2009
DOI: 10.2527/jas.2008-1231
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fiber for pregnant sows: Influence on sow physiology and performance during lactation1

Abstract: This study was conducted to investigate the effects of feeding sows a bulky diet during gestation on their physiological and metabolic adaptations during the peripartum period, and to determine how these effects may relate to sow and piglet performances. From d 26 of gestation until farrowing, gilts were fed diets that contained 2.8 or 11.0% crude fiber (control and high-fiber diets, respectively, n = 9/group). Daily feed allowance provided the same amount of DE daily (33 MJ of DE/d). Throughout lactation, sow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
99
6
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(116 citation statements)
references
References 27 publications
9
99
6
2
Order By: Relevance
“…Similarly, maximal increase in blood glucose level during the OGTT in this study performed post partum was higher and occurred later in time than in OGTT performed in late gestation (Kemp et al, 1996;van der Peet-Schwering et al, 2004). In line with this study and the previously mentioned studies of Kemp et al (1996) and van der Peet-Schwering et al (2004), the results of intravenous glucose tolerance tests performed on sows at day 109 of gestation and at day 4 of lactation confirm that glucose halflife is shorter in late gestation than in early lactation (Quesnel et al, 2009). Different explanations can be given for the basal hyperglycemia and decreased glucose clearance rate observed in early lactation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, maximal increase in blood glucose level during the OGTT in this study performed post partum was higher and occurred later in time than in OGTT performed in late gestation (Kemp et al, 1996;van der Peet-Schwering et al, 2004). In line with this study and the previously mentioned studies of Kemp et al (1996) and van der Peet-Schwering et al (2004), the results of intravenous glucose tolerance tests performed on sows at day 109 of gestation and at day 4 of lactation confirm that glucose halflife is shorter in late gestation than in early lactation (Quesnel et al, 2009). Different explanations can be given for the basal hyperglycemia and decreased glucose clearance rate observed in early lactation.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, levels of leptin in sows can vary in relation to the feeding level (Quesnel et al, 2009), feed composition, time after transition from one feed to another (Papadopoulos et al, 2009) and body condition, mostly measured as back fat thickness (Prunier et al, 2001). In this study, both feeding scheme and body condition of all sows were similar, resulting in similar fasting leptin levels at the first day of lactation for both treatment groups.…”
Section: Discussionmentioning
confidence: 57%
“…It is not clear, however, which mechanism is responsible for these beneficial effects on colostrum yield. Quesnel et al (2009) reported a numerically greater colostrum yield in sows fed a high-fiber diet compared with a low-fiber control diet from day 26 of gestation until parturition (3.4 v. 3.0 kg), although the difference was not significant. Recently, Loisel et al (2013) investigated the influence of the level and source of DF on colostrum yield.…”
Section: Sow Nutrition and Piglet Survivalmentioning
confidence: 89%
“…However, growing evidence shows that restricted feeding during gestation has a negative effect on the welfare of sows, which in turn affects their reproductive performance (Douglas et al, 1998;Sekiguchi and Koketsu, 2004). Previous studies have shown that high-fiber diets could be used to increase the feeling of satiety of gestating sows without providing them with too much energy (Robert et al, 2002), thereby increasing their lactation feed intake and improving reproductive performance (Guillemet et al, 2007;Quesnel et al, 2009). However, lactation feed intake responses to dietary fiber are inconsistent, depending heavily on fiber source (Holt et al, 2006;Darroch et al, 2008), fiber types (Darroch et al, 2008) and the duration sows receive the fibrous diet (Veum et al, 2009).…”
Section: Introductionmentioning
confidence: 99%